327 Difficulties emerging from the end-of-life care in the pediatric intensive care units. (11th October 2021) - Rubic, Filip; Curkovic, M; Jankovic, S; Brajkovic, L; Jozepovic, A; Novak, M; Filipovic-Grcic, B; Borovecki, A
Abstract : Working in ICUs that involves care for critically ill children is inherently demanding. The intricacy of end-of-life issues in this setting adds additional layer of high demands that health care professionals are inadequately prepared for An interpretative, qualitative inquiry based on thematic data analysis using focus groups as data collection method was used in order to get insight into front line, health care staff experiences with end-of-life issues. The study was undertaken in three distinct research sites in the Republic of Croatia and involved health care staff participants (physicians and nurses) from six health care institutions (six NICUs and six PICUs). A total of 21 physicians and 25 nurses participated in eight focus groups. Analysis revealed two main themes, that were equal among professional groups as well as NICU and PICU units. Theme critically ill child consisted of child, family, myself, and other professionals subthemes. Theme end-of-life procedures consisted of subthemes: breaking point, decision-making, end-of-life procedures, 'spill-over' and the four walls of the ICU. Perceptions and experiences of end-of-life issues by nurses and physicians working in NICU and PICU share multiple common characteristics. Interrelatedness of high emotional and cognitive demands and burden associated with end-of-life issues in this setting seems to have a significant influence on personal and professional lives of professionals. Additionally, high variability of end-of-life applied procedures, and various difficulties experienced during shared decision-making process, stresses the need for developing guidelines that will inform such a practice, while considering specific perspectives of everyone involved.